Effect of degree of porosity on the properties of poly(vinylidene fluoride-trifluorethylene) for Li-ion battery separators - Costa, Carlos M. (2012)
Abstract: Poly(vinylidene fluoride-trifluorethylene) porous membranes were prepared by solvent evaporation at room temperature for lithium ion battery separator applications. Microporous membranes with varying pore size and overall porosity are obtained and the thermal, mechanical and electrical properties of the membranes were evaluated before and after liquid uptake of an electrolyte solution of 1 M LiClO4-PC. The electrolyte solution does not change the phase of the polymer and the membranes separators exhibited good thermal and mechanical properties until 100 ºC. The electrolyte solution improves the ionic conductivity of the microporous membranes with the ionic conductivity decreasing with increasing degree of porosity of the membranes. The electrical results obtained for the membranes were compared to the ones obtained for Celgard separators.